Employment insecurity and employees' health in Denmark - Elena Cottini; Paolo Ghinetti (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2016)
We use register data for Denmark (IDA) merged with the Danish Work Environment Cohort Survey (1995-2000-2005) to estimate the effect of employment insecurity on health for a sample of Danish employees. We consider two health measures from the SF-36 Health Survey Instrument: a vitality scale for general wellbeing and a mental health scale. We use three dimensions of perceived employment insecurity: the fear of job loss (job tenure insecurity), of being transferred against will (job status insecurity) and of not finding another job if the current one is lost (employability insecurity). The nature of the dataset enables us to account for both individual and firm fixed. Results show that, overall, employment insecurity matters for both health measures. All the three insecurity dimensions increase psychological distress of workers, while general wellbeing is negatively affected mostly by employability prospects. We also exploit within country variability in employment protection rules by tenure and between blue and white collars to analyse differences in the health effect of our insecurity measures over these dimensions. We find substantial heterogeneity by tenure (attenuated effects by increasing tenure especially for job tenure insecurity) and occupation (white collars are worse off in their health gradient compared to blue collars).
Keywords: I12; J81; J65; 330; job insecurity; employability; mental health; vitality; individual plus firm fixed effects